Physicochemical and textural characteristics of jerky-style pet treats developed with ground swine pluck - Almendares S., Kristian J. (Zamorano: Escuela Agrícola Panamericana, 2024)
Pet food and treats are having a sustainable contribution to the co-products of the meat processing industry. Converting raw material into high protein, fat, and mineral products with specific nutritional components. Swine pluck (SPL) is the combination of heart, trachea, esophagus, and lungs removed together. The objective of this study was to create jerky-style pet treats from upcycling with swine pluck, to evaluate physiochemical and textural characteristics of treats and the proximal analysis (moisture, ash, protein, and fat content) of the optimal treatment. Raw SPL was grinded and mixed with different concentration (0.5, 0.75, 1%) of guar gum (GG) to provide structure, extruded into jerky strips, refrigerated overnight at 4°C and then dehydrated at 68°C for 6 hours. Water activity, pH and cook loss and hardness were determined with their respective methods. A CRD was used, and data was analyzed as a one-way ANOVA using the GLM procedure of SAS, separated by a Duncan multiple range test was done with an alpha of 0.05. PH, water activity and hardness values were higher in concentrations of 0.75 and 1% of GG, and samples were lower in cooking loss analysis in comparison to the control treatment. For proximal analysis, the samples with 0.75% resulted in a high crude fat of 27.6%, protein content of 53.6%, low moisture 10.0% and ash content of 1.4%. The minimal process of co-products combined with a structure forming agent provides a high-value attractive option for both the meat processing industry and pet food industry.